A Construction of Entrepreneurial Personality Tests: Testing Archetype Personality Inventory in Entrepreneurship - Bimo Wikantiyoso; Benedicta Prihatin Dwi Riyanti; Angela Oktavia Suryani (International Journal of Applied Business and International Management, 2021)
VUCA is about a hyper-competitive and unpredictable environment. It stands for volatility, uncertainty, complexity, and ambiguity. Personal attributes are necessary to navigate the VUCA environment. Studies in entrepreneurship show that narratives help people to connect different experiences. Literature shows that a narrative journey can be described through archetypes and relate to entrepreneurial behavior. This study aims to construct and validate measurements of entrepreneurial personality by adapting Pearson & Marr's archetype inventory test within the entrepreneurial context. This study was conducted as an assessment of the measurement psychometric attributes consisting of 12 archetypes. Explanatory Factor Analysis (EFA) was carried out by Oblimin rotation resulting in 60 final items. This study involved 154 small and medium entrepreneurs in Jakarta and West Java.